TI_GERICHTE 15.2010.38 vom 31. Mai 2010 , Procedura di allestimento e di impugnazione della graduatoria fallimentare - TI Tribunale d'appello (2010)
Procedura di allestimento e di impugnazione della graduatoria fallimentare